THE CULTURE OF SPEECH DEVELOPS COMMUNICATIVE SKILLS - PhD, dots. Petrosyan Nelya Valerevna (Western European Studies, 2024)
This article is dedicated to problem of critical thinking and speech culture. Communicative competence is considered one of the main categories of speech culture, so it is important to know the basic communicative qualities of speech, such as accuracy, consistency, richness, diversity of speech, purity and expressiveness. Critical thinking abilities are closely related to speech components, namely normative, communicative and ethical.
Keywords: Culture; speech; critical; thinking